Drafting during swimming improves efficiency during subsequent cycling - Delextrat, A.; Tricot, V.; Bernard, T.; Vercruyssen, F.; Hausswirth, C.; Brisswalter , J. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: The aim of the present study was to investigate the effects of drafting (i.e., swimming directly behind a competitor) while swimming with a wet suit on physiological parameters and cadence during subsequent cycling.